2023
DOI: 10.1093/infdis/jiad512
|View full text |Cite
|
Sign up to set email alerts
|

Varicella Zoster Virus Downregulates Expression of the Nonclassical Antigen Presentation Molecule CD1d

Renee Traves,
Tara Opadchy,
Barry Slobedman
et al.

Abstract: Background The non-classical antigen presentation molecule CD1d presents lipid antigens to invariant natural killer T (iNKT) cells. Activation of these cells triggers a rapid cytokine response providing an interface between innate and adaptive immune responses. The importance of CD1d and iNKT cells in varicella zoster virus (VZV) infection has been emphasised by clinical reports of individuals with CD1d or iNKT cell deficiencies experiencing severe, disseminated varicella post-vaccination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Prior studies revealed that subjects deficient in NK cells or CD1d molecule experience life-threatening varicella following infection or vaccination ( 33 35 ). Thus, we leveraged our scRNAseq dataset to understand the SVV-induced transcriptional changes in NK cell subsets.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies revealed that subjects deficient in NK cells or CD1d molecule experience life-threatening varicella following infection or vaccination ( 33 35 ). Thus, we leveraged our scRNAseq dataset to understand the SVV-induced transcriptional changes in NK cell subsets.…”
Section: Resultsmentioning
confidence: 99%
“…iNKT cells play an important role in microbial infections. Their importance is evidenced by the fact that in some infections, pathogens adopt strategies to reduce CD1d expression ( 61 , 62 ). Although iNKT cells constitute a small population of T cells with a poor diversity of TCR, they enhance as well as regulate immune responses through the recognition of various glycolipid ligands ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%